2022
DOI: 10.3390/jcm11051254
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Plaque Psoriasis in Poland: Disease Severity, Prevalence of Comorbidities, and Quality of Life

Abstract: The epidemiology of psoriasis has not been widely assessed in Polish population so far. This study aimed to investigate psoriasis epidemiological situation by evaluating disease course and severity, management, comorbidities, environmental factors, and knowledge about this disorder among psoriatic patients in Poland. A cross-sectional cohort population-based study enrolled 1080 psoriatic patients and 1200 controls. The mean age of psoriasis onset was 27.6 years; 78.24% had type I psoriasis. Positive family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
5
9
0
3
Order By: Relevance
“…This study obtained outcomes consistent with already available data. 14,15 In this study, gender disparity analysis indicated that male patients had higher prevalence of tobacco smoking, alcohol drinking and tea drinking, had younger age of smoking and alcohol drinking initiation, with longer duration of tobacco smoking and alcohol drinking than female patients. Moreover, male patients had elder age of disease initiation and longer disease duration than female patients, and the prevalence of diabetes, hypertension, hyperlipidemia, and metabolic syndrome in male patients were higher than female patients.…”
Section: Discussionmentioning
confidence: 59%
“…This study obtained outcomes consistent with already available data. 14,15 In this study, gender disparity analysis indicated that male patients had higher prevalence of tobacco smoking, alcohol drinking and tea drinking, had younger age of smoking and alcohol drinking initiation, with longer duration of tobacco smoking and alcohol drinking than female patients. Moreover, male patients had elder age of disease initiation and longer disease duration than female patients, and the prevalence of diabetes, hypertension, hyperlipidemia, and metabolic syndrome in male patients were higher than female patients.…”
Section: Discussionmentioning
confidence: 59%
“…The turn of the millennium ushered in a new therapeutic era as monoclonal antibodies and fusion proteins, also known as biologics, revolutionized the antipsoriatic treatment of patients with moderate to severe plaque psoriasis. Those patients have a high need for medical care 1–3 . In fact, psoriasis was reported to be the third most frequently treated disease in German dermatology clinics 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Those patients have a high need for medical care. [1][2][3] In fact, psoriasis was reported to be the third most frequently treated disease in German dermatology clinics. 4 With the introduction of the interleukin (IL)-17 and IL-23p19 inhibitors for the treatment of plaque psoriasis, the efficacy has reached new heights, with more patients than ever achieving an excellent treatment response (i.e., ≥ 90% clearance of psoriatic lesions [Psoriasis Area and Severity Index, PASI 90 response], and full remission [PASI 100 response]) in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis ist eine häufig vorkommende, chronische, immun-mediierte Erkrankung der Haut, welche aufgrund ihrer moderaten bis schweren Ausprägung bei vielen Patient:innen einer systemischen Therapie bedarf. 1,2 Diese systemische Therapie der Psoriasis wurde durch die Einführung von bestimmten monoklonalen Antikörpern und Fusionsproteinen (auch Biologika genannt) revolutioniert und seitdem stetig um besser wirksamere Substanzen erweitert (zuletzt anti-Interleukin-17-und anti-Interleukin-23-Antikörper). Aktuelle Analysen zeigten jedoch, dass 14,6-78,4% der Patient:innen im klinischen Alltag nicht für Zulassungsstudien dieser Arzneimittel in Frage gekommen wären.…”
unclassified